Portable seawater desalination tank - Roslan, Muhammad Sufi; Abd Rahman, Misbahul Muneer; Azli, Wan Nur Hidayah; Zainudin, Muhammad Aiman; Ma’som, Nazmi (Penerbit UTHM, 2020)
As a result of the hot and dry weather caused by the El Nino phenomenon or the overheating weather that struck our country, water supply dams and rivers supplying raw water resources for water treatment plants in all state were declined (Termizi, 2017). Among the causes of clean water shortage is the pollution due to the poor waste management without systematic method, causing pollution and contamination to the water sources. In the meantime, many countries have also presented some issues with less favourable facilities, especially the problem cause by the lack of clean water at the coastal area (Hirschman, 1975). Thus, portable seawater desalination was developed using condensation concept and distillation methods to produce clean water sources for coastal visitors as well as the use of local residents as an alternative to the dry season.